An unexpected new flightless dung beetle species (Coleoptera: Scarabaeidae: Scarabaeinae: Endroedyolini) from the Cederberg Mountains, South Africa - Daniel, Gimo M.; Strümpher, Werner P.; Deschodt, Christian M. (Zootaxa, 2022)
Silvaphilus joselmae Daniel, Strümpher & Deschodt, new species is diagnosed and described from the Cederberg Mountains, South Africa. The tribal affiliation of Silvaphilus Roets & Oberlander, 2010 is briefly discussed. We revise some generic characters and update the key for the species and genera in the tribe Endroedyolini Davis, Deschodt & Scholtz, 2019. We also provide a distribution map of the two Silvaphilus species.